O-006 Rapid Infliximab Infusion in Children with Inflammatory Bowel Disease: A Multi-Center North American Experience. (February 2017) - El-Matary, Wael; Samson, Charles; Crim, Alisa; Ali, Sabina; Grossman, Andrew
Abstract : Background: Infusions of infliximab (IFX), a chimeric monoclonal antibody against tumor necrosis factor alpha (TNF-α) used to treat inflammatory bowel disease (IBD), can lead to development of anti-IFX antibodies (ATI), increasing risk of subsequent infusion reactions (IRs). IRs have been reported in as many as 5% of infusions and up to 10% to 20% of patients. The safety of rapid IFX infusion has been under-evaluated in children. In a multi-center study, the incidence of IRs associated with rapid infusion of IFX was examined. Methods: The medical records of consecutive children (< 21 yr) with IBD receiving rapid IFX infusions between January 2014 and August 2016 were reviewed. Variables examined included duration of IFX treatment, duration of infusions, time interval between infusions, reported immediate and delayed infusion reactions, pre-medications before the infusions, if any, and presence or absence of concomitant immunomodulators with IFX. Results: A total of 955 rapid infusions for 74 children (mean age 14.4 + 3.1 yr, 41 males, 54 Crohn's disease, 19 ulcerative colitis, and 1 IBD-U) were included. A minimum of 3 induction infusions (median: 8 doses, IQR: 3–13 doses) were administered over the standard time of 2 to 3 hours followed by rapid infusions over 60 minutes for maintenance. The mean dose for IFX was 6.9 mg (range 4.8–15)/kg/infusion. Only 6 participants (8%) had IRs with rapid infusions. The incidence for immediate IRs was 0.3% and delayed IRs was 0.4%. None of these reactions was severe enough to result in discontinuation of IFX. Pre-medications included none (6 participants), acetaminophen (59 participants), anti-histamines (19 participants) and steroids (5 participants)*. Forty one (55.4%) participants were on concomitant immunomodulators. In a univariate logistic regression analysis, the presence of pre-medications, concomitant immunomodulators and IFX dose did not result in any significant effect on the incidence of IRs. *Several patients had more than one medication simultaneously. Conclusions: Rapid IFX infusions over 60 minutes are safe and well-tolerated in children with IBD. This strategy may save significant time and health resources for both patients and healthcare providers. Larger prospective well-designed studies are needed to confirm our conclusions.